Male intrasexual aggression and partial dominance of females over males in vervet monkeys - Saccà, Tommaso; Gort, Gerrit; van de Waal, Erica; Hemelrijk, Charlotte K. (Frontiers in Ecology and Evolution, 2022)
Females dominate a subset of the males in a minority of mammalian species despite male-biased sexual dimorphism. How this may arise is suggested by a computational model, DomWorld. The model represents male-biased sexual dimorphism through the males’ greater initial dominance and higher intensity of aggression, meaning that fights initiated by males have a greater impact than those by females. The model shows that female dominance over males increases with a greater proportion of males in the group. This happens because when males are involved in a larger fraction of fights this results in greater hierarchical differentiation (i.e., steepness). This causes rank overlap between the sexes (i.e., partial female dominance). We test the validity of these processes in vervet monkeys (Cercopithecus pygerythrus), a primate species with partial female dominance. We confirm that the proportion of males in the group is significantly positively correlated with the degree of dominance by females over males and with the steepness of the hierarchy among males exclusively, but not with the steepness of the hierarchy among all adults of the group. The steepness in male hierarchies correlated positively with female dominance over males in these groups. We show that steeper hierarchies among vervet males resulted from male-to-male fights being a larger proportion of the fights among all adults of the group. We conclude that the higher frequency of male intrasexual aggression favours female dominance in vervet monkeys. We also show that females received coalitionary support when they were in conflict with a male, mainly from other females, and that this favours female dominance in this species, but this does not explain why partial female dominance increased with the proportion of males in the group. We advocate further investigation of the influence of male intrasexual aggression on the degree of female dominance over males in other species with partial female dominance.